Self-Reported Awareness and Use of International Classification of Disease Coding of Inflammatory Bowel Disease Services by Ontario Physicians - Forough Farrokhyar; Kevin McHugh; E Jan Irvine (Canadian Journal of Gastroenterology)
RATIONALE: Population and health services research can be performed by linkage analysis of administrative data. However, the robustness of study results is determined by the accuracy of the diagnostic coding.